PENGEMBANGAN MEDIA KOMIK DIGITAL BERBANTUAN CANVA UNTUK MENINGKATKAN MINAT BELAJAR PADA MATERI NEGARAKU INDONESIA PELAJARAN PPKn KELAS IV SDN 105359 SUMBEREJO - Yunanda, Novika Apri; Sujarwo, Sujarwo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education is an important process that is part of human life. Agood learning process begins with wise planning. To reduce the emergence of barriers to learning. Teachers need to prepare learning tools that guide educational staff and stusents to think creatively and be able to adapt to current developments to produce stundents who are only active, creative,and innovative . Based on the result of the result of the researcher’s observations in learning activities on Negaraku Indonesia material during the classs IV PPKn lesson process at SDN 105359 Sumberejo, problem were found in the ongoing PPKn learning. The problems found include, teachers rarely use media in the learning process, student’s low interest in learning when following lessons that have been taught by the teacher during the lesson, in civics learning teachers are more focused by using the lecture method where the teacher focuses on explaning and students only listen and take notes.Students are bored with the learning that is taking place because the teacher is jst monotonous about text books. Based on the problem encountered from the results’ interest in learning. The solution that can be implemented is by using learning media and learning modelsthat can attract students’ enthusiasm for learning. One of the appropriate media and learning models to increase students’ interest in learning in civics lessons is digital comic media and the cooperative Think Talk Write (TTW) learning models. The aim of this research is to analyze the validity, practicality and response of students to Canva-based digital comic media using the cooperative think talk write model to increase students’ interest in learning about Negaraku Indonesia material for grade IV PPKn lessons at SDN 105359 Sumberejo. The research method used in this research is research and development (R&D) with a 4D model (define,design,development, dissemination). From the result of the research, the average validity valuewas 3.62 ‘’valid’’, the practicality score of 3.71 met the practicality criteria. From interest in learning towards digital comic media using Canva in the material My Country, Indonesia obatained a validity percentage of 77.3% of the 15 instrument items. Questionnaire distriuted to 20 students. With percentage results to reach the ‘’Decent’’ category